ISLAMIC MAQASHID APPROACH ON DROPSHIPPING PRACTICES - Abdullah, Muhammad Wahyuddin; Asniati (International Journal of Research -GRANTHAALAYAH, 2021)
Dropshipping is a streamlined form of retail business. In this business, there are three actors involved; buyers, sellers (owners of goods), and drop shippers. The series of product sales through the dropshipping system is when the customer has paid for a product to the drop shipper. The drop shipper then pays the seller as well as sends the products ordered by the customer. Furthermore, the owner of the goods will send the product ordered by the customer directly. This study aims to explain the scheme of buying and selling online through the dropshipping system from the Islamic economic perspective. This research is descriptive qualitative research by analyzing the dropshipping from the Islamic perspective. The study concluded that dropshipping trading is allowed in the perspective of Islamic economics by using the syirkah contract, known as syirkah wujuh and simsarah (broker/agent). Both types of this transaction can legalize dropshipping as long as there are no elements of gharar/frauds. This dropshipping practice is following maqashid syariah which will provide a rational and substantial pattern of thinking in looking at forms of transactions to respond to the progress of growing business.